Effect of water flow on the release flux of dense non-aqueous phase liquids from the riverbed–take dichloromethane as an example. Issue 7 (28th July 2021) - Zhang, Yi; Han, Longxi; Chen, Bo; Wang, Chenfang
Abstract: This research is intended to study the effect of water flow on the release flux of DNAPLs, which have been deposited on the riverbed surface after sudden water pollution accidents. Those contaminants will slowly diffuse from the riverbed into the overlying water body through hydrodynamic action, causing ongoing and serious water pollution. By taking dichloromethane as a typical contaminant, the release form under different hydrodynamic conditions was observed through flume experiments, and the response relationship between the release flux and hydrodynamic factors was analyzed, with an emphasis on parameterizing the release rate. The results suggested that stronger water disturbance significantly enhanced the release of contaminants. And the relationship between the release flux and hydrodynamic factors generally followed an exponential distribution (R 2 > 0.94). Besides, the mathematical relationships between the release flux and the average flow velocity, shear force and turbulent intensity were established as follows: F = 183.63 × e 0.332 u -, F = 617.78 × e 22.292 τ and F = 119.03 × e 2.127 TKE . Thus, this study has offered a solution to solve the source term quantification problem of the differential equation of convective diffusion, which can provide the basis for further developing the mathematical models of this kind of pollutants.